STUDY OF CONTROL OF ACID WATER AT COAL MINING PT. INDONESIA ENERGY CARITAS LADANG PANJANG VILLAGE, SAROLANGUN REGENCY, JAMBI PROVINCE - Dery Armiansyah, (ReTII, 2021)
PT. Caritas Energi Indonesia conducts coal mining using an open pit mining system so that its mining activities are directly related to the outside air. The problem lies in acid mine drainage, especially in the mining pit area because it is closest to the surrounding settlements, at PT. Caritas Energi Indonesia has water discharge in the field, which is known by looking at the staff level, then 26.55 m3/hour settling pond comes from the bottom of sump pit 5 with an area of ​​1.3 hectares. The acid mine water must also be neutralized to comply with quality standards so as not to have a negative effect on the surrounding environment. Acid mine drainage (AAT) or acid mine drainage (AMD) acid rock drainage (ARD) is defined as acid mine water that has been polluted by the oxidation process of sulfide minerals found in rocks as a result of exploration activities or exploitation of mining materials to produce water. under acidic conditions (pH less than 7). Acid mine water is formed from the mineral oxidation process accompanied by the presence of water, thus the 3 main components that cause the formation of acid mine water, namely: sulfide minerals, water, oxygen. Based on the analysis of acid mine drainage before being treated in the mining pit in the research area, the water condition has an average outlet pH for 7 months and has not reached the quality standard, so it is necessary to correct the water pH so that the pH of the water is stable by observing or rearranging the liming process. From the results of testing 1 liter of acid mine drainage with an initial pH of 5, lime is given at a dose of 0.5 g, the pH value of acidic water becomes 7 and this value includes environmental quality standards. Liming is done once every 120 minutes, so 1 day liming is done 2 times. The amount of lime used in one liming is 360 kg so that in a day it takes 1440 kg of lime or 29 sacks. So to neutralize all acid mine drainage from the sump pit, it takes 21 days with 30,240 kg of lime or 605 sacks. Keywords : Acid Mining Water, Environmental Quality Standards, Liming